2010
DOI: 10.1021/ja9106385
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Contributions to Charge Storage in Highly Ordered Mesoporous Group V Transition Metal Oxides with Iso-Oriented Layered Nanocrystalline Domains

Abstract: Amphiphilic block copolymers are very attractive as templates to produce inorganic architectures with nanoscale periodicity because of their ability to form soft superstructures and to interact with inorganic materials. In this paper, we report the synthesis and electrochemical properties of highly ordered mesoporous T-Nb(2)O(5), L-Ta(2)O(5), and TaNbO(5) solid solution thin films with iso-oriented layered nanocrystalline domains. These oxide materials were fabricated by coassembly of inorganic sol-gel reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
292
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(312 citation statements)
references
References 50 publications
11
292
0
Order By: Relevance
“…37 However, prior research does not indicate whether one particular phase of Nb2O5 is better than another. While the pseudohexagonal phase of Nb2O5 (TT-Nb2O5) is preferred in electrochromic applications, the tetragonal phase (MNb2O5) has shown the best performance when integrated in the electrode materials for lithium ion batteries.…”
Section: Figure 4 Xps (Top) and Xrd (Bottom) Pattern Of Nb2o5 Deposimentioning
confidence: 99%
“…37 However, prior research does not indicate whether one particular phase of Nb2O5 is better than another. While the pseudohexagonal phase of Nb2O5 (TT-Nb2O5) is preferred in electrochromic applications, the tetragonal phase (MNb2O5) has shown the best performance when integrated in the electrode materials for lithium ion batteries.…”
Section: Figure 4 Xps (Top) and Xrd (Bottom) Pattern Of Nb2o5 Deposimentioning
confidence: 99%
“…It is interesting to note that the synthesis of Nb 2 O 5 described in Ref. 13 resulted in Nb 2 O 5 electrodes with no initial Li and minimal contaminants, based on X-ray photoelectron spectroscopy data. 13 Pseudocapacitance has also been demonstrated with MnO 2 involved in reversible redox reactions with H + , K + , and Li + .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the electrochemical performance of NiO nanocrystals largely depends on its microstructure, surface area, and the presence of dopants [30][31][32][33][34][35], suggesting that the development of controlled syntheses of NiO nanostructures with the desired features, e.g., high electronic conductivity, low diffusion resistance to protons/cations, and high electroactive area is of paramount importance. Although several other techniques-such as surfactanttemplate [36], sol-gel [37][38][39], anodization [40], and hard template [41][42][43] methods-have been reported for synthesizing porous nanocrystals, solvothermal/ hydrothermal techniques [3,30] are of particular interest as they are flexible and can be readily adapted to large scale production. Herein, we report a facile way to synthesize porous NiO nanoslices, nanoplates, and nanocolumns with adjustable surface area, and that these NiO nanostructures show a structure-dependent specific charge capacitance.…”
Section: Introductionmentioning
confidence: 99%